Perubahan Mutu Fisik dan Mikrobiologi Gel Cincau Hijau Kemasan selama Penyimpanan - Endang Prangdimurti; Dian Herawati; R. Dani Briantoto (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
Traditional green grass jelly has a limited shelf life due to its poor microbiological and physical (syneresis) properties. Improvement of green grass jelly quality has been done by reformulation of the jelly with the combination of thermal application (steaming and pasteurization). The objective of this research was to study the stability of physical and microbiological properties of steamed (CHK) and pasteurized (CHP) green grass during storage at low temperature (5-100C). CHP have greater syneresis than CHK, with the level of syneresis reaching 6.66% and 4.90%, respectively, on the 15th day of storage. In general, up to 15 days of storage, CHK could preserve its quality better than CHP, in term of syneresis level, texture, and green color. It was also shown that pH is one parameter that is stable during the storage of both CHK and CHP, which is ranged between 6.5-7.3. The microbiological quality of both fresh and stored pasteurized jelly contained fewer microorganisms (1 log) than the steamed jelly. Pasteurized green grass jelly has a prolonged shelf life until 12 days of storage at refrigerated temperature.